Gaya Berpacaran dalam Perspektif Etis Teologi dan Iman Kristen - Opur, Elsheca Patiman; Kristiani, Kristiani (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2025)
The rise of the times today makes many young people, especially young Christians, choose to enjoy things that are not worth doing in dating. Young people are often curious about the name sex or making love, they want to try and do things that they often see or watch, not only that there are factors from outside that make their curiosity even greater in terms of relationships or the word making love. A good dating style according to the Christian faith is very necessary among young people because holiness needs to be done and is important in starting a holy relationship. The purpose of this writing is to provide understanding, knowledge and understanding to every young person about a good and correct dating style according to theological ethics and Christian faith. The discussion that is written uses a qualitative method by using literature review writing techniques or literature studies. The results of the study show that the dating period is a period of introduction to the nature, mindset, background of life before entering into a marriage relationship. Dating relationships in Christianity are a period of introduction